Sampling events from the Tara Pacific Expedition 2016-2018 - Guillaume Bourdin; Guillaume Iwankow; Fabien Lombard; Stephane Pesant; Clémentine Moulin; Emilie Boissin; Julie Poulain; Sarah Romac; Sylvain Agostini; Bernard Banaigs; Emmanuel Boss; Chris Bowler; et al. (PANGAEA, 2022)
The Tara Pacific expedition (2016-2018) sampled coral ecosystems around 32 islands in the Pacific Ocean, and sampled the surface of oceanic waters at 249 locations, resulting in the collection of nearly 58,000 samples. The expedition was designed to systematically study corals, fish, plankton, and seawater, and included the collection of samples for advanced biogeochemical, molecular, and imaging analysis. Here we provide the dataset obtained with a small CTD probe (Castaway CTD) deployed from the dinghy down to the reef (generally ~5 to 10m) to record temperature and conductivity profiles.